Pendekatan Konseling Pastoral Bagi Lansia Yang Mengalami Loneliness - Jenny Huberta Kotta, Chalma; Erastus, Stephen; Santoso, Sugeng; Michael Najoan, Junius; Martin Tamera, Daniel (Vox Dei: Jurnal Teologi dan Pastoral, 2024)
This article discusses the importance of a pastoral counseling approach in helping older adults who experience loneliness. Loneliness is a common social problem experienced by the elderly due to changes in the social environment and social loss that often occurs with age. Researchers used a qualitative method with a literature study approach, through journal articles, books, and internet media as data used in this study. The discussion that will be discussed is the concept of loneliness in the elderly, how pastoral counseling can be an effective approach in overcoming it. The results found are the important role of pastoral counselors in providing emotional support, providing spiritual encouragement, and building deep relationships with elderly people who feel lonely. Through this pastoral counseling approach, researchers provide three approaches, namely, 1) social support, 2) listening, 3) community services that can help elderly people who experience loneliness and find new meaning in life and improve the quality of life of the elderly.